Targeting Polymorphonuclear Leukocytes in Acute Myocardial Infarction - Clara Di Filippo; Francesco Rossi; Michele D'Amico (The Scientific World Journal)
Several studies have recognized the strong impact that the acute myocardial infarctions (AMI) have on the morbidity and mortality of patients affected by cardiovascular diseases. Still open, however, is the field concerning the mediators and the pathways involved in the etiology of this cardiovascular event. The present review would support the relatively new discovered role that the polymorphonuclear leukocytes (PMNs) have in the pathogenesis of the AMI, through a brief analysis of past and ongoing research. Particularly, it is reviewed here the possibility that inhibition of the activity of PMNs and inhibition of the signaling pathways related to their activity may result useful in AMI and may improve the prognosis of this pathology. This review, indeed, presents and discusses new data on one of the lipid kinase, the phosphoinositide 3-kinase gamma (PI3Kγ), and its role in neutrophil recruitment during AMI.